Estudo anatomorfológico, radiográfico e tomográfico de Schistosomus reflexus em ovino da raça Dorper: relato de caso - Ferreira, D.o.l. [UNESP]; Santarosa, B.p. [UNESP]; Monteiro-toma, C.d. [UNESP]; Belotta, A.f. [UNESP]; Chiacchio, S.b. [UNESP]; Machado, V.m.v. [UNESP]; Gonçalves, R.c. [UNESP]; Prestes, N.c. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2013)
Schistosomus reflexus (SR) is a rare and fatal congenital anomaly, primarily observed in ruminants, presenting fetus with dorsiflexion of the vertebral column, exposure of thoracic and visceral organs, and scoliosis. A caesarian was performed on a Dorper sheep on a farm in Botucatu-SP and according to the general characteristics and findings observed in the necropsy of the fetus it was an SR case. The radiography indicated a marked ventro-dorsal deviation of the thoracolumbar column segment and deformity of the ribs. On the computed tomography the integrity of the bones and organs were detected, except for the absence of a lumbar vertebra. No data were available in the literature for SR diagnosis in sheep by image, so radiographic and tomographic exams of the fetus were done.

O Schistosomus reflexus (SR) é uma anomalia congênita fatal e rara, primariamente observada em ruminantes, a qual apresenta feto com dorsoflexão da coluna vertebral, exposição das vísceras abdominais e torácicas e escoliose. Foi realizada uma cesariana de ovelha da raça Dorper, em propriedade da região de Botucatu-SP. Pelas características gerais e achados de necropsia, tratava-se de um caso de SR. A radiografia revelou acentuado desvio ventrodorsal do segmento da coluna vertebral toracolombar e deformidades das costelas. Na tomografia computadorizada, observou-se presença da integridade dos ossos e órgãos, exceto ausência de uma vértebra lombar. Não havia dados na literatura de diagnóstico por imagem de SR em ovinos, portanto procedeu-se, de forma inédita, a exames radiográfico e tomográfico do feto.
Anatomorphological, radiographic and tomographic studies of Schistosomus reflexus in Dorper breed sheep: case report
Keywords: defeitos congênitos; monstruosidade fetal; ruminantes; radiografia; tomografia computadorizada; congenital defects; fetal monstrosity; ruminants; radiography; computed tomography